1989
DOI: 10.1111/j.1472-765x.1989.tb00252.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement by cationic compounds of the growth inhibitory effect of novobiocin on Escherichia coli

Abstract: The inhibitory effect of low levels of novobiocin on the growth of Escherichia coli was greatly enhanced by the presence of cationic compounds which alone produced no inhibitory effect. Diaminoacetone and spermidine were the most effective enhancers of the novobiocin effect, but N‐(2‐pyrimidinyl)‐piperazine, methylglyoxyl‐bis‐(guanylhydrazone), agmatine, 3,3‐diamino benzidine and 3‐amino benzamidine also produced marked enhancement. There was slightly less effect of 4,5,6‐triamino pyrimidine, pyridoxamine and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

1997
1997
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 9 publications
2
6
0
Order By: Relevance
“…This has been shown to be the case with the enzymatic derivative of PMB, PMB nonapeptide, whose antimicrobial activity is markedly reduced with respect to PMB while, as a permeabilizer, it retains the potency of its parent molecule ([ 41 ], and our own unpublished results). Observations similar to ours have been reported by others using agents of disparate nature including spermidine and other polyamines ([ 42 , 43 ], cholic acid derivatives [ 44 ] as well as cationic steroid antibiotics [ 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…This has been shown to be the case with the enzymatic derivative of PMB, PMB nonapeptide, whose antimicrobial activity is markedly reduced with respect to PMB while, as a permeabilizer, it retains the potency of its parent molecule ([ 41 ], and our own unpublished results). Observations similar to ours have been reported by others using agents of disparate nature including spermidine and other polyamines ([ 42 , 43 ], cholic acid derivatives [ 44 ] as well as cationic steroid antibiotics [ 45 ].…”
Section: Discussionsupporting
confidence: 88%
“…A possible reason for this is that SPP forms a complex with gentamicin ; SPP complexes with other drugs and forms an insoluble precipitate with chlorhexidine ( Ayres 1995). The high potentiating action of SPP had also been shown by other workers ( Vaara 1992) while Modha et al . (1989 ) demonstrated that cationic compounds such as spermidine could increase the growth‐inhibitory properties of novobiocin against E. coli .…”
Section: Discussionsupporting
confidence: 79%
“…with concnetration ----------------------------------------------------------------------------------------- ------------------------------------------------------------------------------------------------------------- --------------------------------------------------------------------------------------------------------------- ----------------------------------------------------------------------------------------------------------- ----------------------------------------------------------------------------------------------------------------For key, see Table 1. insoluble precipitate with chlorhexidine (Ayres 1995). The high potentiating action of SPP had also been shown by other workers (Vaara 1992) while Modha et al (1989) demonstrated that cationic compounds such as spermidine could increase the growth-inhibitory properties of novobiocin against E. coli.…”
Section: Discussionmentioning
confidence: 59%
“…Several agents have been used in attempts to alter the OM permeabilities of gram-negative bacteria (4); these include EDTA and lysozyme (2, 13), sodium hexametasulfonate (26), detergents like sodium dodecyl sulfate (1) and deoxycholate, as well as permeabilizing portions of antibiotics such as polymyxin B (18,23) and other compounds containing positively charged amino groups, such as spermidine and lysine (24) and methylglyoxal bis-guanylhydrazone (16).…”
Section: Discussionmentioning
confidence: 99%